Potential Failure Mode In Pergau Spillway - Mohd Zaini, Mohamad Zulhisyam (Universiti Sains Malaysia, 2022)
Various potential failure modes in the field of hydraulic structure, focussing on the spillway dam, are due to overtopping, erosion, and structural stability. With enough time, these phenomena can damage the concrete surface of a chute spillway. Influencing factors that damage the spillway, such as spillway discharge, velocity and pressure along the spillway and geometry of the spillway itself, will be discussed in this paper. In order to predict these potential failures in a chute spillway, a numerical analysis using various numerical techniques with different software is proposed. This paper aims to simulate the Effect of the Free Surface Water Level, Cavitation of a High-Speed Flow, and Cracking Risk due to Structural Stability on the Pergau Spillway. Four different reservoir levels of 638.4, 639.4, 640.4 and 641.08 m simulation setup are done to evaluate the relationship of reservoir level with the mentioned purpose of this paper. The 3D CFD model is validated using data extracted from the studies of the spillway. For free surface water level study, highest maximum principal stress is calculated 231910 Pa at reservoir level of 640.4 m and the lowest minimum principal stress is calculated 159600 Pa at reservoir level of 641.08 m. This indicates that there is no expected structural failure due to the free surface water level effect. For cavitation of a high-speed flow study, the cavitation area decreases from reservoir level 638.4m (3508.57 m2) to 640.4 m (2183.089 m2), then slightly increases at 641.08 m (2674.331 m2). It is found that the maximum discharge does not automatically cause the minimum cavitation number (higher area of cavitation number).